HUBUNGAN PEMBINAAN MENTAL DAN PRESTASI AKADEMIS DENGAN KOMPETENSI TARUNA DI BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (BP2IP) TANGERANG, BANTEN - Suriadi (LP. Ma'arif Janggan Magetan, 2020)
Abstract: Central Education Science and Training Service (BP2IP) Tangerang is a government institution under the Board of Education and Training Ministry of Transportation and technically built by Center for Education and Training of the Sea (Pusdiklat), which has a goal to educate and assist candidates with the benefits of sea competitiveness of competence, according to standard national and Internasional. to achieve this are required to BP2IP Tangerang can result student in the field of service with the students competency with high standards, according to the observation that the author student Competency will influenced by the Development of Mental and Moral. Research is focused on analyzing the data and facts on the ground about the influence of Mental and Moralof student competence in BP2IP Tangerang. Unit of analysis in this research is the student of BP2IP Tangerang. Research method used is descriptive analytical that is using a method that is verifikatif with the goal to test a hypothetical, the research that takes a sample from one population and the use of questionnaires as a means of primary data collectors, data analysis in accordance with the most problems is the analysis and correlation regression, where variables of Mental and Moral as independent variables, and the Quality of Competency as dependent variables. Abstrak Balai Pendidikan dan Pelatihan Ilmu Pelayaran (BP2IP) Tangerang merupakan salah satu lembaga pemerintah di bawah Badan Pendidikan dan Pelatihan Departemen Perhubungan yang secara teknis dibina oleh Pusat Pengembangan Sumber Daya Manusia (PPSDM) Perhubungan Laut, yang mempunyai tujuan untuk mendidik serta membina calon- calon pelaut dengan keunggulan daya saing kompetensi, sesuai standar national dan Internasional. Untuk mencapai tujuan tersebut BP2IP Tangerang dituntut untuk dapat menghasilkan Taruna di bidang pelayanan dengan standar Kompetensi Taruna yang tinggi. Hal inilah yang menarik untuk diteliti secara stastik. Unit analisis dalam penelitian ini adalah adalah Taruna BP2IP Tangerang. Metode penelitian yang digunakan adalah menggunakan deskriptif analitis yaitu suatu metode yang bersifat verifikatif dengan tujuan untuk menguji suatu hipotesis, yaitu penelitian yang mengambil sampel dari satu populasi dan menggunakan kuesioner sebagai alat pengumpul data yang pokok, Analisis data yang paling sesuai dengan permasalahan adalah analisis korelasi dan regresi, dimana variabel Pembinaan Mental dan Prestasi Akademis sebagai variabel independen, dan Kualitas Kompetensi Taruna sebagai variabel dependen.